Current trends in digital transformation of public administration - Nataliia Pasenko (Науковий вісник Мукачівського державного університету. Серія Економіка, 2022)
The digitalisation of public administration is a process aimed at improving access to goods and services. The demand for facilitating access to services, in particular public services, and boosting the economy, to which the digital transformation can contribute, makes this study relevant. The purpose of this study is to analyse current trends in the digital transformation of public administration and public authorities. The study employed general scientific methods, in particular analysis and synthesis, and comparative methods. Areas for improving the efficiency of decision-making by public authorities through the use of information and communication technologies and digitalisation were considered. It has been substantiated that the intensified use of the latest information technologies in providing various services by public authorities determines the beginning of the formation of its own model of digitalisation of public administration. The digital transformation of public administration is defined as a problem-solving tool for the society that can provide significant savings in public expenditure, benefiting the administration and the citizens, whose daily needs and concerns are placed at the centre of public administration strategies. The impact of digitising services for citizens has been shown to be effective, in particular in facilitating access to and use of services. The necessary conditions for successful digital transformation were identified